Optimization of the parameters of mobile antennas of HR range - N. I. Listopad; D. A. Kovalevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The study results of parameters of main high-frequency range mobile antennas are presented: whip antenna, sloping wire antenna, inverted V symmetrical vibrator (dipole), T-shaped antenna, sloping V antenna, NVIS, traveling wave antenna, λ-shaped antenna. The analysis of the input active and reactive resistances of the antennas, as well as standing wave ratio is performed depending on the frequency. The corresponding graphical dependencies are presented.